Language Use and Identity in Minority Hungarian and Hungarian–Romanian Deaf Families. (3rd March 2022) - Belenyi, Emese; Flora, Gavril
Abstract: This paper discusses language use and identity patterns in families set up by deaf partners living in Romania, where at least one of the spouses belongs to the ethnic Hungarian minority. Language use and transmission of identity to children in ethnically homogenous (Hungarian) or heterogeneous (Hungarian–Romanian) families of deaf are explored. The research is based on a survey conducted among members of the ethnic Hungarian Deaf community (including ethnic Romanian spouses), life-path interviews with selected deaf persons and interviews with special school educators. The research results denote that in the case of deaf people living in ethnically homogeneous marriages who graduated from Hungarian language special school the transmission of Hungarian identity, Hungarian sign language/oral language knowledge—combined with the components of Deaf culture—tends to be a natural and usually undisturbed process. However, if one of the spouses is Romanian, the language of communication within the family will probably be the Romanian sign language/oral language. On the other hand, in the families where ethnic minority and ethnic majority family members are present, with typical and atypical hearing, complex, multifaceted linguistic communication models might prevail, favoring specific multicultural modes of intrafamilial identity development and transmission.